PENYULUHAN KESEHATAN TENTANG PERILAKU SEDENTARY DI PUSKESMAS JOHAR BARU, JAKARTA - Prabawati, dewi; Khristiana Blegur, Mariana (Jurnal Abdimas Musi Charitas, 2020)
Community service, especially health services, considered as an important prevention action toinhibit non-communicable diseases’ complication, which held in collaboration with Public healthcenter. This community health services aimed to increase health status through monitoring bloodpressure, fasting blood glucose, and motivating society to perform physical activities to decreasesedentary behaviour which have positive correlation with obesity, hypertension, thus inducesdevelopment of metabolic syndrome. Increase level of knowledge on physical activity andsedentary behaviour for non-communicable diseases patients need to be highlighted, in terms ofcontrolling glycaemic index, metabolic control and cholesterol level. The community healthservice was held to 39 participants of Prolanis (Program of chronic diseases management)members at Johar Baru Public health center, Jakarta. As the results, there were 84.6%participants who have sedentary behaviour >17.1 hour/day. Most of the participants also havehigh risk factors such as hypertension, obesity and hyperglycaemia. It is expected that the Prolanismember should modify their lifestyle by performing physical activity regularly, such as walking,cleaning the house or other health activities to prevent complication